“Smile and please hide your sickness”: The role of emotions and sickness surface acting in a presenteeism climate context - Correia Leal, C.; Ferreira, A.I.; Carvalho, H. (20th EURAM Annual Conference, 2020)
The study of emotional labor and presenteeism climates in the hospitality industry is crucial due to nowadays context of economic uncertainty and the ambient of insecurity, that forces employees to continue to show up for work despite being sick. The aim of this research was exploring the effects of two antecedents of surface acting on hotel employees’ burnout levels. Moreover, we introduced sickness surface acting – the voluntary effort to suppress illness symptoms or to fake a healthy health status - as a new construct to explain the relation between presenteeism climate and burnout. A total of 166 employees from Portuguese hotel chains completed a 5-day diary survey. From these, 58 reported at least one day working while being ill. Study 1 results showed that surface acting mediated the relationship between both anger and presenteeism climate and burnout. Study 2 revealed that, for sick employees, sickness surface acting mediated the relationship between presenteeism climate and burnout. These findings highlight the importance of policies creation to reduce and manage anger and presenteeism climates negative consequences, as well inform human resources managers of the negative impacts of “service with a smile” and sickness presenteeism in the hotel industry.